(3eNJUQ ef GdMSGHs - (3eMeO Hf GdMSf Hf EHQGgje GdYWGQ GdGTYQj, GHf Gdbjes
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GYde Cf GdMSGH KdGKI eQGJH s
(3BNQgG (B:s
(3ef BNQ GdehLhO KdGKI CQHGY hNeS hGdKeGfjI hGdNeSjf CQHYI CNeGS hSOS , hGdJSYI hGdNeSjf JSYI CYTGQ s
(3Vef eLehY , JQJjHgG (B: 9s
(3HBNQg ahGFO MSGHjIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3BjGUhajG (B(3757) s
Keywords: (3eJaQbGJs